Perang di Tambang Minyak: Sosial Ekonomi Bajubang pada Masa Perang Revolusi - Sari, Ratna Eka; Pradita, Dennys (UIN Sunan Gunung Djati Bandung, 2023)
This research examines the economic impact of the wartime on Bajubang in the late 1940s. The Bajubang is an oil mining area that has economic and political value for the Netherlands. can be independent. This study will discuss how the socio-economic dynamics of the Bajubang were during the war and also how they affected people's lives. This study uses historical methods with an economic approach. The economy of a region will experience problems when there is war, this also happens in the Bajulang region. The Bajubang area, which has oil mines, is constrained by the war and is also one of the targets for attacks by Dutch troops. The existence of this chaos caused a halt in mining and also the economy in this region